2021
DOI: 10.1038/s41598-021-87772-0
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of vernacular and modernising dwellings in three climatic zones to climate change

Abstract: Climate change impacts buildings in multiple ways, including extreme weather events and thermal stresses. Rural India comprising 65% of the population is characterised by vernacular dwellings evolved over time to passively regulate and maintain comfortable indoors. Increasing modernization in rural habitations (transitions) evident from the ingress of modern materials and electro-mechanical appliances undermines the ability of building envelopes to passively regulate and maintain comfortable indoors. While suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Even ISO 7730 mentioned adaptation, wherein people in warm climates can accept hot environments compared to colder climates (Standard, 2005). This is also conforming to the study done by Shastry et al (2016), Henna, Saifudeen, and Mani (2019), Saifudeen and Mani (2021) where the occupants exhibit a more comprehensive comfortable temperature range in free-running buildings against the adaptation study mentioned in Fanger (1973). An exciting study held during the COVID-19 pandemic period in Italian and French classrooms in the same climate zone observed that the neutral temperature of French students was 3.1 °C less than their Italian counterparts.…”
Section: Thermal Adaptationsupporting
confidence: 88%
“…Even ISO 7730 mentioned adaptation, wherein people in warm climates can accept hot environments compared to colder climates (Standard, 2005). This is also conforming to the study done by Shastry et al (2016), Henna, Saifudeen, and Mani (2019), Saifudeen and Mani (2021) where the occupants exhibit a more comprehensive comfortable temperature range in free-running buildings against the adaptation study mentioned in Fanger (1973). An exciting study held during the COVID-19 pandemic period in Italian and French classrooms in the same climate zone observed that the neutral temperature of French students was 3.1 °C less than their Italian counterparts.…”
Section: Thermal Adaptationsupporting
confidence: 88%
“…The climates of nation are more varied as a result of this extensive coastline [35][36][37]. Thus, diversification and climate change directly impact architecture, construction materials, and energy consumption in buildings, which is considered to be currently one of the main global problems [38][39][40]. To address this issue, some nations are proposing various building energy efficiency plans and initiatives that take climate zoning into account.…”
Section: Field Of Study and Climatic Zoningmentioning
confidence: 99%
“…In recent years, Asian vernacular case studies have been the most assessed in regard to indoor thermal comfort [3,7,[16][17][18][19][20][21][22][23][24][25]8,26,27,[9][10][11][12][13][14][15] (60% of the analysed research), covering a wide variety of humid climate locations, which may be due to not only the prevalence of vernacular architecture at these locations but also the extensive availability of case studies that retain their residential functions. These are then followed at a considerable distance by Portuguese vernacular dwellings [2,5,28], in a Mediterranean hot-dry climate, generally built with local materials such as earth (adobe brick, rammed-earth), stone and wood, and dating back as far as the 17th century, and Iranian vernacular dwellings [29][30][31], mixing earth, brick, and limestone, in a hot-dry and hot-humid tropical climate.…”
Section: Main Features: Case Studies Location Climate and Building Ma...mentioning
confidence: 99%
“…The simulation of vernacular dwellings is a developing research field that allows, inter alia, to obtain long-term performance predictions for a validated model, perform sensitivity and parametric analyses for improving overall performance and comfort, and examine climate change resilience and its impact on thermal comfort. In the past years, it has mainly been applied to assess thermal performance and bioclimatic strategies [22,26,[53][54][55]39,[46][47][48][49][50][51][52], thermal comfort [15,17,38,42,20,23,25,29,[32][33][34][35], energy consumption [23,55], illuminance [56], and computational fluid dynamics [57]. This section highlights the key findings stemming from the analysis of the most relevant recently published research on the simulation of vernacular dwellings for thermal performance and comfort analysis, amounting to 26 publications.…”
Section: Modelling Vernacular Dwellings: Analysis Of Researchmentioning
confidence: 99%